2019
DOI: 10.3390/ma12233962
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive Multi-Walled Carbon Nanotube/Epoxy Strain Sensor with Pattern Design

Abstract: Carbon nanotube/polymer-based composites have led to studies that enable the realization of low-cost, high-sensitivity piezoresistive strain sensors. This study investigated the characteristics of piezoresistive multi-walled carbon nanotube (MWCNT)/epoxy composite strain sensors subjected to tensile and compressive loads in one direction at relatively small amounts of strain. A patterned sensor was designed to overcome the disadvantage of the load direction sensitivity differences in the existing sensors. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…30 Hwang et al also showed for CNTs in epoxy resin a positive influence of reduced thickness on GF. 71 Meng et al applied a layer of graphene platelets on an elastomer substrate and found out that for thinner graphene layer thickness GF increased. 72 Yu et al printed a polymer 3D network and embedded CNTs in the surface.…”
Section: Discussion On the Influence Of Yarn Count On Gfmentioning
confidence: 99%
“…30 Hwang et al also showed for CNTs in epoxy resin a positive influence of reduced thickness on GF. 71 Meng et al applied a layer of graphene platelets on an elastomer substrate and found out that for thinner graphene layer thickness GF increased. 72 Yu et al printed a polymer 3D network and embedded CNTs in the surface.…”
Section: Discussion On the Influence Of Yarn Count On Gfmentioning
confidence: 99%
“…The advantages of using MWCNTs instead of pure ones lie in the additional advantages of the processed materials added to the composites. Scientists have tried different mixed kinds of polymers and nanoparticles to enhance the quality of MWCNT nanocomposite-based sensors [ 102 , 103 , 104 ]. These sensors have proven to have higher sensitivities in terms of G.F., lower response time, and lower hysteresis.…”
Section: Multi-walled Carbon Nanotube (Mwcnt)-based Strain Sensorsmentioning
confidence: 99%
“…These results verified that MWCNT/epoxy composite sensors could be applied to real-time structural health monitoring. 17 Ku-Herrera and Avilies also focused on the piezoresistive behavior of MWCNT/vinyl ester composites under axial tension and compression for use in structural health monitoring and smart detection systems. They found that the piezoresistive behavior of the composite material was linear and reversible in tension for all levels of applied strain since the vinyl ester thermosetting matrix was brittle in tension.…”
Section: Introductionmentioning
confidence: 99%